Analisa Willingness To Pay Melalui Healthy Food Tamu Hotel Di Masa Adaptasi Kenormalan Baru Di Hotel Aviary Bintaro - Nicko Gana Saputra; Asmawih; Ajeng Julyani Ryzanti (Politeknik Sahid, 2021)
This research aims to analyze the characteristics of healthy food consumers among hotel guests during the new normal adaptation period at Hotel Aviary Bintaro, determine the average willingness to pay value for healthy food among hotel guests during the new normal adaptation period at Hotel Aviary Bintaro, and identify the factors that influence the willingness to pay for healthy food at Hotel Aviary Bintaro. The data analysis used in this research is quantitative, including validity and reliability tests. The research was conducted at Hotel Aviary Bintaro. The population of this study is hotel guests at Hotel Aviary Bintaro. The collected data will be processed and described quantitatively.